Professional Quality of Life Among Physicians and Nurses Working in Portuguese Hospitals During the Third Wave of the COVID-19 Pandemic - Serrão, Carla; Martins, Vera; Ribeiro, Carla; Maia, Paulo; Pinho, Rita; Teixeira, Andreia; Castro, Luísa; Duarte, Ivone (Frontiers in Psychology, 2022)
Background: In the last two weeks of January 2021, Portugal was the worst country in the world in incidence of infections and deaths due to COVID-19. As a result, the pressure on the healthcare system increased exponentially, exceeding its capacities and leaving hospitals in near collapse. This scenario caused multiple constraints. Previous studies reported that COVID-19 has had significant negative impacts on healthcare workers’ psychological health, including stress, anxiety, depression, burnout, post-traumatic stress symptoms, and sleep disturbances. However, there are many uncertainties regarding the professional quality of life of hospital nurses and physicians. To address gaps in previous research on secondary traumatic stress, we focused on healthcare workers working in hospitals affected by a major traumatic event: the third wave of COVID-19. Objectives: The primary aim of the present study was to identify the contribution of personal and work-related contextual variables (gender, age, parental status, occupation, years of experience, working with patients affected by COVID-19) on professional quality of life of healthcare workers. Methods: Cross-sectional study with a web-based questionnaire given to physicians and nurses working in a hospital setting. A total of 853 physicians and nurses (median age 37 years old) participated. Factors of professional quality of life were assessed using regression analysis. Results: Most of the participants showed high (80%) or moderate (18%) levels of compassion satisfaction, whereas the majority of them experienced moderate levels of burnout (72%) and secondary traumatic stress (69%). The analysed variables demonstrated no differences between professionals who were directly or not involved in the care of COVID-19 patients. Parental status was found to be a significant factor in compassion satisfaction. Female was significantly associated with more susceptibility to secondary traumatization. Factors that may potentially contribute to burnout include years of professional experience and the number of work hours per week. Conclusions: The COVID-19 pandemic has created a new challenge for the healthcare system. Burnout and secondary traumatic stress can lead to medical errors and impact standards of patient care, particularly compromising compassionate care. It is therefore recommended that hospitals develop psychoeducational initiatives to support professionals in dealing with barriers to compassion.